Livestock-water productivity in the Nile Basin: Solutions for emerging challenges - Amede, Tilahun; Descheemaeker, Katrien K.; Mapedza, Everisto D.; Peden, Donald G.; Breugel, P. van; Awulachew, Seleshi Bekele; Haileslassie, Amare (Springer, 2011)
The competition for water between different uses and users is increasing, particularly in the Nile basin where about 90% of the production systems comprise livestock. There is an ongoing debate on how to increase water productivity in these crop-livestock systems. This paper presents a comprehensive framework to provide policy guidance and promote action to improve returns from water investments through: (i) provision of sufficient watering points for livestock across the basin; (ii) improving water productivity through promoting water-saving technologies, ensuring system integration and control of transboundary flux of livestock diseases; and (iii) formulating participatory basin scale regulatory frameworks on water use and sharing. It also argues that improving water productivity through integrated technological, policy and institutional interventions offers an opportunity for smallholders in both upstream and downstream countries to adapt to climate and market risks.